Neoliberal Homophobic Discourse: Heteronormative Human Capital and the Exclusion of Queer Citizens - Peterson, David (Journal of homosexuality, 2011)
In this article, I examine the relationship between homophobic language use and its broader social context, focusing on how a U.S.-based, conservative Christian organization's institutionalized homophobic text-making practices seek to derive legitimacy from the broader political economic discourses associated with the neoliberal moment. Using the Family Research Council's statement on marriage and the family as the basis for analysis, I demonstrate how the organization seeks to represent lesbian and gay subjects and their kinship formations as a threat to human capital development because they are based on affectional relationships that neither reflect nor respond to the kinds of self-governance and marketization that neoliberalism requires of all citizen-subjects and their families. Linguistic strategies for creating such representations include lexical choices that avoid overtly identifying lesbian and gay subjects as the object of discussion, the creation of a taxonomy for what constitutes "proper" families-based on neoliberal principles-that implicitly excludes lesbian and gay kinship formations, and the use of neoliberal discourses of self-governance and marketization as the basis for that exclusion.